Cleaning and disinfection of environmental surfaces in the context of COVID-19 : interim guidance : 15 May 2020 (World Health Organization, 2020)
The purpose of this document is to provide guidance on the cleaning and disinfection of environmental surfaces in the context of COVID-19. This guidance is intended for health care professionals, public health professionals and health authorities that are developing and implementing policies and standard operating procedures (SOP) on the cleaning and disinfection of environmental surfaces in the context of COVID-19.
Keywords: Betacoronavirus; infekce spojené se zdravotní péčí; Coronavirus Infections; Equipment Contamination; hygiena; epidemický výskyt choroby; dezinfekce; infekční lékařství; Disease Outbreaks; koronavirové infekce; Disinfection; COVID-19; Cross Infection; kontaminace zdravotnického vybavení